1981
DOI: 10.1111/j.1365-2133.1981.tb00801.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary influences on 8-MOP plasma levels in PUVA patients with psoriasis

Abstract: To study the effect of diet on 8-MOP plasma levels, these levels were measured three times in twenty PUVA patients with psoriasis; while fasting, after a low-fat breakfast, and after a fat-rich breakfast. No significant differences were found between the maximal 8-MOP plasma levels in the fasting condition and the levels after the low-fat breakfast, both peaking 2 h after ingestion. After the fat-rich breakfast, however, the 8-MOP plasma levels were not only significantly lower at 2 h but also peaked later, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The differences between these two studies are probably due to the differences in drug formulations and in the composition of the standard diet. Roelandts et al (1981a) found that a lowfat meal did not affect the absorption phase of a plasma concentration-time curve whereas a highfat breakfast caused a significant decrease in methoxsalen concentrations at the time of UV A irradiation. Due to the short sampling time in this study, which was performed in 8 patients, Cmax, tmax and AUC could not be calculated.…”
Section: Influence Of Foodmentioning
confidence: 96%
“…The differences between these two studies are probably due to the differences in drug formulations and in the composition of the standard diet. Roelandts et al (1981a) found that a lowfat meal did not affect the absorption phase of a plasma concentration-time curve whereas a highfat breakfast caused a significant decrease in methoxsalen concentrations at the time of UV A irradiation. Due to the short sampling time in this study, which was performed in 8 patients, Cmax, tmax and AUC could not be calculated.…”
Section: Influence Of Foodmentioning
confidence: 96%
“…Several authors [1,6] have clearly demonstrated that the absorption of 8-MOP varies significantly according to the composition of the meal which accompanies the ingestion of the drug.…”
Section: Commentsmentioning
confidence: 99%
“…Concomitant intake of food can affect both the rate and the extent of drug absorption [11][12][13], and consequently it might be important to standardize the Correspondence to: H. Ehrsson, Karolinska Pharmacy, Box 160, S-17176 Stockholm, Sweden food intake in relation to the administration of the psoralens. The influence of food on the pharmacokinetics of 8-MOP has been studied [14][15][16]. However, no general conclusions can be drawn from these studies with regard to the food effect, since different drug formulations and diet compositions have been used.…”
mentioning
confidence: 99%